Cassane and nor-cassane diterpenoids from the roots of Erythrophleum fordii. (June 2020) - Li, Lulu; Chen, Long; Li, Yuhuan; Sun, Shikai; Ma, Shuanggang; Li, Yong; Qu, Jing
Abstract: Detailed phytochemical investigation of the roots of Erythrophleum fordii furnished seven undescribed cassane-type diterpenoids, erythrocassanoids A-E and erythro-norcassanoids A, B and two known clerodane diterpenes, 15-hydroxy-3-cleroden-2-one and methyl ester of 2-oxopopulifolic acid. Their structures were determined by 1D, 2D NMR and HRESIMS analysis. The antiviral activities of these compounds were evaluated. Among them, 15-hydroxy-3-cleroden-2-one and methyl ester of 2-oxopopulifolic acid showed antiviral activities against influenza virus and coxsackie virus with IC50 values ranging from 11.11 to 29.60 μM. Graphical abstract: Image 1 Highlights: Seven undescribed cassane-type diterpenoids were isolated and identified from the roots of Erythrophleum fordii. Two undescribed diterpenoids were rare nor-cassane type diterpenoids. Some compounds showed antiviral activities with IC50 values ranging from 11.11 to 29.60 μM.